A Comprehensive Comparative Study on the Injection of Autologous Whole Blood Versus Corticosteroid for Lateral Epicondylitis - Awez Khan; Bhimani Fahad Wahid; Mukesh Tiwari; Rajesh Kumar Kanoji; Pradeep Kumar Suthar (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Background: Lateral epicondylitis, commonly known as tennis elbow, is a common musculoskeletal condition affecting the extensor tendons of the forearm, specifically the common extensor tendon originating at the lateral epicondyle of the humerus. Individuals engaged in professions or sports that involve frequent and forceful use of the forearm, such as carpentry, painting, or playing racquet sports, are at an increased risk. Objective: The objective is to compare the efficacy, in terms of pain relief and functional improvement, of autologous whole blood and corticosteroid injection in managing lateral epicondylitis. Methods: This was a comparative study conducted in the Department of Orthopedics, National Institute of Medical Sciences Jaipur, Rajasthan, India. Eighty patients diagnosed to be having lateral epicondylitis were included in this study on the basis of predefined inclusion and exclusion criteria. A detailed history was obtained in terms of the presence of any chronic system illness such as hypertension, diabetes mellitus, arthritis, or any autoimmune disorder. The patients were divided into 2 groups on the basis of whether they were given autologous whole blood (Group B) or corticosteroid injection (Group S). The efficacy of both the treatment modalities was compared in terms of Pain relief (as assessed by a reduction in Visual Analogue Score [VAS] score) and functional improvement (as assessed by an improvement in the Mayo Elbow performance score). SSPS 22.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: A total of 80 patients were included in this study out of which there were 37 (46.25%) males and 43 (53.75%) females with a M: F ratio of 1:1.16. The mean age of patients in Group B and Group S was found to be 52.36±9.98 years and 48.46±10.12 years, respectively. The mean age of patients in both groups was found to be comparable with no statistically significant difference (p=0.0866). In this study, till 2 weeks after injection, the reduction in VAS score was found to be comparable in both groups. At the time of 4 weeks, 8 weeks, and 12 weeks follow–up, the mean VAS score in Group B was less as compared to Group S, and the difference was found to be statistically highly significant (p<0.0001). At the time of 4 weeks, 8 weeks, and 12 weeks follow-up, the mean MEPS in Group B was more as compared to Group S, and the difference was found to be statistically significant (p<0.05). Conclusion: It is concluded that both interventions exhibited a favourable safety profile, with minimal and manageable adverse effects. However, for lateral epicondylitis, whole blood injection demonstrated superior efficacy in terms of pain relief and functional improvement as compared to injection of corticosteroid.